Facile method for the construction of random nanoparticle arrays on a carbon support for the development of well-defined catalytic surfaces - Baron, R; Campbell, F; Streeter, I; Xiao, L; Compton, R (2008)
A simple and easy way to construct platinum nanoparticle (PtNPs) arrays on a carbon matrix is presented and the catalytic properties of the developed materials are evidenced with electrochemical studies. Technically, the key point resides in being able to get metallic nanoparticles of homogeneous size that are well dispersed on a carbon substrate. Specific efforts in this direction led us, here, to obtain, for the first time, well-defined and well-spread PtNPs of 100 ± 40 nm on carbon microspheres. The resulting material was used for the development of a low cost practical Pt nanoelectrode array sensor for aqueous proton detection. In addition, methanol oxidation was studied to exemplify potential uses in fuel cells. The procedures described are very simple to apply and represent an original strategy for the development of well-defined catalytic surfaces. © 2008 by ESG.